Effects of inducing apoptosis and inhibiting proliferation of siRNA on polyadenylate‐binding protein‐interacting protein 1 in tongue cell carcinoma. Issue 12 (21st August 2020) - Xie, Huixu; Yang, Lisa; Hu, Qin; Song, Yingqi; Wang, Xiaoyi; Zhou, Liming; Li, Longjiang
Abstract: Background: It has been reported that the polyadenylate‐binding protein‐interacting protein 1 (PAIP1) pathway is closely connected with the progression of some malignant tumors. Here we examined the potential functional mechanism of PAIP1 in tongue squamous cell carcinoma (TSCC). Methods: PAIP1 was knocked down in TSCC cell lines and proliferation and apoptosis in vitro analyzed. The molecular features of TSCC were determined using quantitative proteome and succinylome analyses. The results were confirmed in the mouse model. Results: PAIP1 promoted cell proliferation and inhibited apoptosis. Its knockdown decreased Ki67 and Pcna expressions and increased Bax/Bcl2 index and Caspase‐3 expression. Bioinformatics analysis for proteomics revealed that PAIP1 knockdown correlated with the changes in differential protein expression. Conclusions: Upregulation of PAIP1 induces cell proliferation and inhibits apoptosis in TSCC; PAIP1 might be a diagnostic biomarker and a significant drug target.